ChemInform Abstract: The Journey of L‐Tartaric Acid in the World of Enantiomerically Pure Bis‐ and Trisadducts of C60 with the Inherently Chiral trans‐3 and All‐trans‐3 Addition Patterns. Issue 52 (29th December 2014) - Chronakis, Nikos
Abstract Review: 21 refs.